Application of POE Based Module in Reaction Rate Material to Improve Students' Critical Thinking Abilities - Agnes Florida Patricia Saragih; Gulmah Sugiharti (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
The use of teaching materials in schools is one of the supports in the learning process. Modules are teaching materials that students can use in learning. This research aims to 1) Determine the level of validity of the module being developed; 2) Knowing the increase in students' critical thinking abilities taught with the modules developed; 3) Knowing students' responses to the modules being developed. The research method is R&D with the 4D development model. Data collection techniques through BSNP questionnaires, student response questionnaires and N-Gain tests to improve critical thinking. The population was Holy Kids Bersinar Medan High School. Based on material and media expert validators, it shows that 84.7% of material experts, 83.75% of media experts, the modules developed have a validity level of "Very valid". The module was also successful in improving students' thinking abilities through pretest and posttest scores that were carried out and the n-gain was searched for and obtained a score of 0.83% in the "High" category. Student responses to the development of this module received score of 93.05 in the "Very Good" category. Thus, it can be concluded that the use of POE-based chemistry modules has been successful in improving students' critical thinking abilities.